A Growth and Adjustment Strategy for Pakistan - Burki, Shahid Javed; Hasan, Parvez (World Bank, Washington, DC, 2014)
This paper is divided into four sections. The first provides a quick overview of the current political and economic situation, focusing in particular on the stagnation of growth and deepening macroeconomic imbalances, and a fast approaching balance of payments crisis. The second section focuses on ways to improve macro-economic balances especially public finances not only by increasing revenues but restructuring expenditures including reductions in subsidies to the non-poor and increasing the effectiveness of public spending. The third section focuses on critical elements in reviving growth. The paper argues for a comprehensive growth strategy which focuses on governance as a central issue. Reversing the decline of public institutions and improving the quality of governance will provide confidence in the country's economic future and will result in increasing domestic investment. Other elements of the strategy must involve improving the energy situation; correcting the long neglect of exports and using international trade as a driver of growth (including opportunities that may become available by the intended normalization of trade with India); reversing the decline on growth rate of agriculture both by supporting diversification in the cropping pattern; processing of agricultural products, and more economical use of inputs (especially water); a new push on human development including quality of education in public schools, skills training and a new emphasis on adult literacy; and, a new compact with the private sector that phases out economic rents, reduces the burden of unnecessary or ineffective regulation not excluding labor legislation, and strengthens incentives for investment and productivity improvements especially in moving up the value added chain. Finally, the fourth section presents a summary of key actions that government could take along with a timeline for implementation.